Variations in the sensitivity of different primers for detecting Wolbachia in Anastrepha (diptera: tephritidae) - Marcon, Helena Sanches [UNESP]; Coscrato, Virgínia Elias [UNESP]; Selivon, Denise; Perondini, André Luiz Paranhos; Marino, Celso Luis [UNESP] (Sociedade Brasileira de Microbiologia, 2011)
Wolbachia are endosymbiont bacteria of the family Rickettsiacea that are widespread in invertebrates and occur between 20% and 60% of Neotropical insects. These bacteria are responsible for reproductive phenomena such as cytoplasmic incompatibility, male killing, feminization and parthenogenesis. Supergroups A and B of Wolbachia are common in insects and can be identified using primers for 16S rDNA, ftsZ and wsp; these primers vary in their ability to detect Wolbachia. The ftsZ primer was the first primer used to detect Wolbachia in Anastrepha fruit flies. The primers for 16S rDNA, ftsZ and wsp and the corresponding PCR conditions have been optimized to study the distribution of Wolbachia and their effect on the biology of Anastrepha in Brazil. In this work, we examined the ability of these primers to detect Wolbachia in Anastrepha populations from three regions in the State of São Paulo, southeastern Brazil. All of the samples were positive for Wolbachia supergroup A when screened with primers for 16S A rDNA and wsp A; the wsp B primer also gave a positive result, indicating cross-reactivity. The ftsZ primer showed a poor ability to detect Wolbachia in Anastrepha and generated false negatives in 44.9% of the samples. These findings indicate that reliable PCR detection of Wolbachia requires the use of primers for 16S rDNA and wsp to avoid cross-reactions and false negatives, and that the ftsZ primer needs to be redesigned to improve its selectivity.
Keywords: Anastrepha; cross reaction; ftsZ; wsp